DRY NEEDLING AND HYPERTENSION EXERCISE IN REDUCING BLOOD PRESSURE AMONG HYPERTENSIVE PATIENTS AT RISK OF STROKE IN CILACAP REGENCY - Muttaqin, Wahyu Wahid; Sodikin, Sodikin; Subroto, Wishnu (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Hypertension is a major risk factor for stroke and a public health issue. Nonpharmacological interventions such as dry needling and hypertension exercise programs serve as complementary approaches to blood pressure control. To evaluate the effectiveness of a combination of dry needling and a hypertension exercise program in lowering blood pressure in hypertensive patients at risk for stroke in Cilacap Regency. A quasi-experimental pretest–posttest study with a control group. Sample: 40 hypertensive patients at risk for stroke, divided into an intervention group and a comparison group. The combination of dry needling and hypertension exercise was administered for four weeks. Systolic and diastolic blood pressure were measured before and after the intervention. Comparative statistical tests were performed with a significance level of p < 0.05. After four weeks, the intervention group showed a significant reduction in blood pressure compared to the comparison group. The average decrease in systolic blood pressure was 20.1 mmHg and in diastolic blood pressure was 11.9 mmHg in the intervention group (p < 0.05). The control group experienced a smaller reduction, and the difference between the groups was statistically significant. The combination of dry needling and hypertension exercises is effective in lowering blood pressure in hypertensive patients at risk for stroke. This study adds to the empirical evidence regarding the effects of dry needling and hypertension exercises on the community population in Cilacap Regency.